Developing online learning guidebook for junior high school level in Kendari City - Darnawati Darnawati; Jamiludin Jamiludin; Mursidin Mursidin; La Ili (Journal of Education and Learning (EduLearn), 2021)
This research aimed to develop online learning guidebook for junior high school level. The method used in this research was research and development in terms of 4-D model development which consists of four main stages: Define, Design, Develop, and Disseminate. The informants were study consisted of 2 expert informants and 17 junior high school teachers in Kendari City, Southeast Sulawesi, Indonesia. This type of research data was descriptive qualitative. The data collected were in the form of suggestions and responses put forward by the informants. This information was collected and summarized to improve the learning products developed. The results showed that the developed online learning guidebook has met the appropriate criteria in the media and language aspects by the respective experts. Besides, Teachers find that this guidebook is very interesting and useful as a guide in online learning, especially during the current pandemic. Furthermore, the developed guide book fosters curiosity of teachers to find out the use of applications in the book, and makes teachers think creatively in making learning media. The online learning guidebook is advantaged for the teachers to provide interesting learning media and material for students especially in this pandemic era.